A novel apatite-inspired Sr5(PO4)2SiO4 plasma-sprayed coating on Ti alloy promoting biomineralization, osteogenesis and angiogenesis. Issue 8 (15th April 2022) - Udduttula, Anjaneyulu; Li, Jian; Ma, Zhen; Teng, Bin; Zhang, Jian V.; Ferreira, Ana M.; Gentile, Piergiorgio; Wang, Guocheng; Zhao, Xiaobing; Ren, Pei-Gen
Abstract: Osteoconductive, osteoinductive, anti-infection, and controlled ionic release properties are crucial for the long-term clinical success of orthopedic and dental metallic implants. In this study, we have successfully synthesized apatite chemical structure mimic Sr5 (PO4 )2 SiO4 (SPS) nanopowder by sol-gel method to be used as a novel bioactive ceramics coatings on medical-grade titanium alloy by plasma-spray deposition technique. The deposited SPS coatings were analytically characterized by XRD and SEM-EDS analysis and confirmed that the coating possessed a pure crystalline phase of SPS without any other secondary phases, and exhibited a sharp needle-like morphology with the existence of Sr, P, O, Si elements. The cross-sectional view proved that the deposition of dense SPS layer with a thickness of 116 μm. The in vitro ionic dissolution behavior of SPS coatings was detected by ICP-OES analysis and confirmed their controlled releasing profile of ions such as Sr (120–55 ppm) and Si (0.14–9.86 ppm). In vitro biomineralization study demonstrated that the SPS coatings were remarkably encouraged the ball likes apatite crystals growth on their surface with a Ca/P ratio (1.677) similar to natural bone minerals. The SPS coatings exhibited notable cellular interactions with human umbilical card-derived mesenchymal stem cells (HUMSCs) in terms of cell proliferation, early-stage differentiation, and calcium nodule accumulation in ECM, also the osteogenic differentiation was found to be prominent for SPS coated Ti64 than sandblasted Ti64. Furthermore, the angiogenic property of SPS coated Ti64 was evaluated by Human umbilical vein endothelial cells (HUVECs) and confirmed their tremendous cell viability with non-toxicity and nominal angiogenic differentiation. Therefore, our study proved that the apatite-inspired SPS bioactive ceramics coatings could improve the biofunctional activities of orthopedic and dental implants for their better clinical success. Graphical abstract: Graphical abstract for plasma sprayed a novel apatite inspired Sr5 (PO4 )2 SiO4 coating on Ti64 and its in vitro biological studies. Image 1